THE DEVELOPMENT OF INDIVIDUALISM IN SOCIETY AND ITS IMPACT ON THE INSTITUTION OF THE FAMILY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article provides information about the importance and history of individualism formed in the West. It also analyzes the conclusions about the functions and role of the universal family institution. Views on the penetration of individualism into the East and its impact on values in the process of today's globalization are studied. Analytical materials are also presented on the fact that individualism and egoism are completely different concepts.